ANALISIS FUNGSI KAWASAN HUTAN LINDUNG, HUTAN PRODUKSI TERBATAS, DAN HUTAN PRODUKSI TETAP DI KABUPATEN KOLAKA TIMUR - Samsi Awal; Ahmad Iskandar; Andri Estining Sejati; Eko Hariyadi (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aims to analyze the functions of protected forest areas, limited production forests and permanent production forests in East Kolaka Regency. This type of research is descriptive quantitative and area survey with the main study being the description of maps of physical factors and non-physical reasons. The research also examines the suitability of the map with the actual conditions in the field. Physical Data Collection Method using ArcGIS 10.4.1 software base map from BAPPEKAB East Kolaka Regency and BMKG. The Data of non-physical factors is the form of data related to inappropriate land use were collected through interviews. Descriptive analysis is presented in the form of: overlay with the scoring equipped, tables of areas and percentages. The criteria for designating a protected forest are fully explained in the Decree of the Minister of Agriculture Number 2837/Kpts/Um/11/1980. The results of the study show that the potential function of the area in East Kolaka Regency consists of Limited Production Forests and Production Forests. Most of the Limited Production Forests are in Ueesi District with 159,709.465 hectares or 40.72%. Most production forests are in Ueesi District with 20,937.437 hectares or 5.33%. The Limited Production Forest Area experienced a difference of 3,214.329 being settlements, dry land agriculture, paddy fields, and transmigration. Production Forest Areas experienced a difference of 64,042.12 into settlements, dry land agriculture, rice fields, and transmigration.